The role of some of the level Antioxidant enzymes and Obesity in development infertility women’s infertility in Najaf Province Patients, IRAQ - Al-hadrawi, Kais Khudhair; ALGarawy, Raid Talib (BIO web of conferences, 2023)
In case-control research, the impact of Obesity and oxidative stress on the emergence of infertility in women was examined. From October to February 2022, I examined 150 clinical samples of women, all female and aged (at childbearing age). Two groups of patients were formed: the first group contained 60 patients with obesity-related infertility in women and 60 patients with non-obesity-related infertility in women. In contrast, the second group contained 30 control subjects who were fertile. Saline blood From each patient, samples were taken. This study adhered to the same ethical standards as the accepted patients who visited the Infertility Center at AL-Sader Medical City in the province of AL-Najaf. Using a gel tube, 3 ml of venous blood was placed to separate the serum and calculate the catalase (CAT), Level of the enzyme Superoxide Dismutase (SOD), and Glutathione peroxidase (GPx) Infertility in Women patients’ serum concentrations of Catalase (CAT), SOD and GPx was found to be significantly lower (P ≤ 0.05) than those of control women. The findings showed a positive correlation with significant differences between catalase andSOD AND GPX, sex hormone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), prolactin ana Teststerone respectively.